2018
DOI: 10.1002/sdtp.12688
|View full text |Cite
|
Sign up to set email alerts
|

22.2: Invited Paper: Sputtered Molybdenum‐Oxide for Anti‐Reflection Layers in Displays: Optical Properties and Thermal Stability

Abstract: Molybdenum (Mo) is commonly used for thin film transistor (TFT) metallization in displays. Apart from its outstanding electronic and adhesive properties in the metallic form, it also possesses stable oxidation states, including sub‐stoichiometric oxides. Depending on the amount of oxygen, the properties can be widely tuned and oxygen‐deficient MoO3‐y films can be electrical conducting and optically absorbing, making them suitable candidates for integration as low‐reflection coatings for on/in cell touch, black… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…The clear area of this metal layer can be used for display and the dark area be as decorations. Aluminum or molybdenum metal layer is used as the substrate, and by adjusting the thickness of the Anti-reflection Film [2,3], colorful devices with different colors and low reflectivity can be obtained. Colorful devices with a low reflectivity of 14-16% and a high transmittance of 73%-74% can be obtained by adding an ITO film layer between the metal layer and the anti-reflection film layer and adjusting the film thickness.…”
Section: Objective and Backgroundmentioning
confidence: 99%
“…The clear area of this metal layer can be used for display and the dark area be as decorations. Aluminum or molybdenum metal layer is used as the substrate, and by adjusting the thickness of the Anti-reflection Film [2,3], colorful devices with different colors and low reflectivity can be obtained. Colorful devices with a low reflectivity of 14-16% and a high transmittance of 73%-74% can be obtained by adding an ITO film layer between the metal layer and the anti-reflection film layer and adjusting the film thickness.…”
Section: Objective and Backgroundmentioning
confidence: 99%
“…Among the applications of molybdenum oxide, substoichiometric molybdenum oxide has gradually received more attention because of its excellent optical, electrical and catalytic properties. In the field of optoelectronics, MoO x can be used in the antireflection layer of displays [ 10 , 11 ], to improve solar energy conversion efficiency [ 12 , 13 , 14 , 15 ] and in new-generation sodium magnesium batteries [ 16 , 17 , 18 ]. In addition, it can also be used in catalysis [ 19 , 20 ], biomedicine [ 21 ], electronic devices [ 22 , 23 ] and other fields.…”
Section: Introductionmentioning
confidence: 99%
“…It can also be stacked with high work function metals, e.g., Ni, and subjected to certain heat treatments for higher stability [ 29 ]. Hennrik Schmidt et al [ 11 ] found that the original amorphous MoO x films prepared by magnetron sputtering began to transform into crystalline MoO 2 films after thermal treatment at 350 °C. It can be observed that this substoichiometric molybdenum oxide exists stably only within a specific temperature range, and the thermal stability, decomposition mechanism and phase generated in the decomposition process have not been studied in detail.…”
Section: Introductionmentioning
confidence: 99%
“…Pachlhofer et al [11] synthesized Mo-O thin films using ceramic MoO x targets with compositions ranging from x = 2.5 to 2.8. To investigate the reflectance of light from external sources and the resulting color impression of the dark layer coatings, Hennrik [25] used ceramic oxide targets to deposit a thin layer of metal oxide.…”
Section: Introductionmentioning
confidence: 99%